1989
DOI: 10.1111/j.2042-7158.1989.tb06453.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for α1-adrenoceptor subtype predominance in the rat seminal vesicle

Abstract: Noradrenaline (0.6-19 microM) and phenylephrine (2-130 microM) induced contractions in the rat seminal vesicle that were competitively antagonized by the alpha 1-adrenoceptor-selective antagonist corynanthine (120-920 nM). Yohimbine (60-450 nM), an alpha 2-adrenoceptor-selective antagonist, produced a non-competitive antagonism of noradrenaline responses, suggesting that the responses were not alpha 2-adrenoceptor mediated. It is concluded that the rat seminal vesicle has a predominance of alpha 1-adrenoceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Such a mechanism was suggested by Sharif et a1 (1990) who performed a detailed study of clonidine on noradrenaline and phenylephrine responses in rat seminal vesicle, concluding that clonidine acted as a competitive antagonist at aI -adrenoceptors. Inhibition of noradrenaline by yohimbine is suggested to be due to antagonism of postjunctional al -adrenoceptors (Adenekan 1989;Sharif et al 1990), since the selectivity of yohimbine between a I -and HASSAN.SADRAE1 ET AL a,-adrenoceptors is in the order of tenfold (Kobinger & Pichler 1980;McGrath 1982). The reported absence of a,-binding sites in this tissue (Shima 1993) is entirely compatible with the effects of clonidine and yohimbine reported above.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Such a mechanism was suggested by Sharif et a1 (1990) who performed a detailed study of clonidine on noradrenaline and phenylephrine responses in rat seminal vesicle, concluding that clonidine acted as a competitive antagonist at aI -adrenoceptors. Inhibition of noradrenaline by yohimbine is suggested to be due to antagonism of postjunctional al -adrenoceptors (Adenekan 1989;Sharif et al 1990), since the selectivity of yohimbine between a I -and HASSAN.SADRAE1 ET AL a,-adrenoceptors is in the order of tenfold (Kobinger & Pichler 1980;McGrath 1982). The reported absence of a,-binding sites in this tissue (Shima 1993) is entirely compatible with the effects of clonidine and yohimbine reported above.…”
Section: Discussionsupporting
confidence: 79%
“…However, there is little information about the functional significance of these peptides, although some authors point to the possibility of co-transmission between noradrenaline and neuropeptide Y , or ATP (Nakanishi & Takeda 1973;Meldrum & Burnstock 1985;Stjernquist et a1 1987;Wali & Greenidge 1989). Of the post-synaptic receptors in rat vesicular smooth muscle, adrenoceptors are mainly of the @,-subtype (Gokhale & Sharif 1983;Adenekan 1989;Sharif et a1 1990), and the cholinoceptors are muscarinic. The nature of any pre-synaptic receptors is unknown.…”
mentioning
confidence: 99%
“…17 The greater effects of these agents in the seminal vesicle than in the vasa deferentia may be related to the predominance of a1-adrenoceptors in the rat seminal vesicle. 18 These results are consistent with those of Hsieh et al, 19 who reported that sympatholytic drugs effectively attenuated contractile responses in the seminal vesicle induced by electrical nerve stimulation of lesser splanchnic nerve in rats. Although the a-blockers included in this study served as a positive, internal control to confirm the viability of this modified rat model, Cavallini demonstrated the therapeutic efficacy of a1-adrenergic blockers (alphuzosin and terazosin) for premature ejaculation in a double-blind, placebo-controlled, crossover clinical trial.…”
Section: Discussionsupporting
confidence: 91%
“…Sympathetic, noradrenergic fibers have been visualized within the smooth muscle layers of the seminal vesicles [6][7][8], in which the release of noradrenaline results in muscle contractions, mediated via otl-adrenoceptors [9,10]. Sympathetic innervation may also be visualized by immunolabeling neuropeptide Y (NPY), which is found in all noradrenergic terminals in the pelvic viscera of male rats [11].…”
Section: Introductionmentioning
confidence: 99%